Reduced dopamine function within the medial shell of the nucleus accumbens enhances latent inhibition - Nelson, Andrew J.D.; Thur, Karen E.; Horsley, R.R.; Spicer, C; Marsden, C.A.; Cassaday, Helen J. (Elsevier, 2011)
Latent inhibition (LI) manifests as poorer conditioning to a CS that has previously been presented without consequence. There is some evidence that LI can be potentiated by reduced mesoaccumbal dopamine (DA) function but the locus within the nucleus accumbens of this effect is as yet not firmly established. Experiment 1 tested whether 6-hydroxydopamine (6-OHDA)-induced lesions of DA terminals within the core and medial shell subregions of the nucleus accumbens (NAc) would enhance LI under conditions that normally disrupt LI in controls (weak pre-exposure). LI was measured in a thirst motivated conditioned emotional response procedure with 10 pre-exposures (to a noise CS) and 2 conditioning trials. The vehicle-injected and core-lesioned animals did not show LI and conditioned to the pre-exposed CS at comparable levels to the non-pre-exposed controls. 6-OHDA lesions to the medial shell, however, produced potentiation of LI, demonstrated across two extinction tests. In a subsequent experiment, haloperidol microinjected into the medial shell prior to conditioning similarly enhanced LI. These results underscore the dissociable roles of core and shell subregions of the NAc in mediating the expression of LI and indicate that reduced DA function within the medial shell leads to enhanced LI.